Experiencing Society and the Lived Welfare State - Haapala, Pertti; Harjula, Minna; Kokko, Heikki (Palgrave Studies in the History of Experience,, 2023)
This open access book presents a new approach to the history of welfare state. By applying the concepts of experiencing society and the lived welfare state, the collection introduces theoretical, methodological and empirical insights for bridging the everyday life and institutional structures. The chapters analyze how the welfare state as a particular individual-society relationship has become an integral part of living in the modern society. With a long-term perspective, the chapters explore the experience of society which enabled the building and the resilience of a welfare state. As the welfare state is not a universal model of social development but historically unique in different contexts, the book broadens the focus from the Nordic countries to Southern Europe, colonial Asia and post-colonial South America. This collection is essential reading for scholars and students in the social sciences and history, as well as for policymakers and practitioners who face the contemporary and future challenges of the welfare states. Pertti Haapala is Emeritus Professor of History and the Director of the Academy of Finland Center of Excellence in the History of Experiences (2018-2021) at the University of Tampere, Finland. His special areas of research are social history and methodology of history. Minna Harjula is University Researcher at the Academy of Finland Center of Excellence in the History of Experiences at the University of Tampere, Finland. Her recent work focuses on social citizenship and the lived construction and legitimation of the Finnish welfare state. Heikki Kokko is Postdoctoral Research Fellow at the Academy of Finland Center of Excellence in the History of Experiences, and Director of the Digital history project Translocalis Database at the University of Tampere, Finland. His current focus is on the historical and theoretical analysis of the experience of society.